(untitled) (United States, 2003)
Developing Writing is a reading and writing skills text designed for beginning to intermediate learners of English. Each of the twenty chapters in this book is introduced by a reading selection that incorporates the lesson’s model structures, mechanics, and grammar points. Each reading in Developing Writing focuses on some aspect of American or world culture. Each reading passage is followed by composition, vocabulary, and spelling activities. An irregular verb list, grammar rule index, and answer key are also included.
Keywords: Tiếng Anh,English language; Dạy và học,Study and teaching